Optimizar y dimensionar la ubicación de los RSU en una red vial mediante modelamiento matemático basado en ILP para determinar la mejor posición en la infraestructura de comunicaciones Vanet - Palacios Sanatana, Héctor Andrés (2016)
This paper presents a mathematical model based on ILP (Integer Linear Programming) and applied to VANET. This model aims to determine the best position and the minimum number of RSUs required for the deployment of a communications network VANET, considering the radius of coverage, capacity, and location of the RSUs and the percentage of vehicles that must be online as restrictions for minimize an objective function by using a software tool to solve the proposed model. In the results, finally you get that to reach 90% coverage, the model optimizes 75% of the RSUs, of which 50% of the RSUs assets used its full capacity, achieving identify the sectors within the area of planning where would be necessary and appropriate activate a new RSU to provide better quality of service.